Mobile application for calendar events of UiTM Perlis branch (CEPS) / Muhammad Nabil Fikri Jamaluddin ... [et al.] - Jamaluddin, Muhammad Nabil Fikri; Abd Saad, Ummaira; Othman, Mahfudzah; Mohd Fauzi, Shukor Sanim; Ibrahim, Alif Faisal; JM Gining, Ray Adderley (UiTM Cawangan Perlis, 2017)
Smartphone nowadays has become a must for everyone to communicate and retrieve important information. Various information about products, events and almost everything are accessible from the fingertips. Recently, method of dissemination of information regarding events in Universiti Teknologi MARA (UiTM) Perlis Branch, is conducted thru posters, flyers and social networking sites. This method of spreading information is not reliable since it still fails to reach the whole community even students, lecturers and staff of the campus. Thus, lead to less number of participation. This project aims to introduce an innovative way of spreading information about events to communities via mobile application. Valuable information includes name of events, date, target audience, organizer and its location will be made available in the application for user. Data is stored in the MySQL database and JSON is used to manipulate it and pass to mobile application to be represented in user interface. User acceptance testing is conducted via questionnaire to check the capability and deliverables of the mobile application to the end users. The overall result shows that the application developed is acceptable and applicable to be used in by the community of UiTM Perlis.